The American civil war in twentieth-century Britain: political, military, intellectual and popular legacies - Tal, N (2013)
This thesis explores the continuous British interest in the American Civil War from the war’s end to the late twentieth century and the British utilisation of the conflict at home and in the Atlantic arena. Contributing to the limited, yet burgeoning literature on the subject, this study emphasises the independent agency of both the Civil War and its British interpreters. It thus rejects a simplistic depiction of British adoption of American culture and applies a more sophisticated methodology that accounts for the active, versatile and autonomous British use of complex foreign images. This enables a meaningful analysis of the Civil War’s place and role in modern British culture. The thesis examines the British fascination with the conflict as reflected in four facets: politics, military thought, academe and popular culture. Additionally, it takes a transatlantic perspective and explores how Britons’ view of the United States has influenced their understanding of the Civil War. This study thus provides a first comprehensive and coherent overview as well as a nuanced picture of the American conflict as it travelled across the Atlantic from a historically distanced perspective. The thesis reveals that the Civil War achieved unique prominence in British culture and that this British fascination with the war was part of a greater transatlantic encounter between an epic American affair and sophisticated British interpreters. Accordingly, the two main questions underpinning this study are ‘why were the British particularly interested in the Civil War?’ and, following directly on that path, ‘how did Britons use the war both at home and in the transatlantic sphere?’ Answering these questions further establishes the war’s prominence in British culture and explores the character of the British encounter with the conflict. In so doing, it contributes to our understanding of the Civil War’s global impact and casts another light on Anglo-American relations.